Clinical and Biological Effects of Adjunctive Photodynamic Therapy in Refractory Periodontitis - Alhabashneh, Rola; A Mashal, Mohammad; Khader, Yousef; Qudah, Rana (Journal of Lasers in Medical Sciences, 2019)
Introduction: To date, no novel treatment approach is available for optimum outcomes regarding refractory periodontitis. The aim of the present study was to assess the efficiency of photodynamic therapy (PDT) in treating patients diagnosed with refractory periodontitis and compare the clinical and biological outcomes of conventional periodontal treatment with or without adjunctive PDT in these patients, by assessing clinical parameters (plaque index [PI], gingival recession [GR], bleeding on probing [BOP], periodontal probing depth [PPD] and clinical attachment level [CAL]) as well as biological parameters (IL-1β) in the gingival crevicular fluid (GCF). Methods: Sixteen patients within the age of 30 to 60 years, with a mean age of 40 years old, diagnosed with refractory periodontitis were included. In this split mouth design study, 2 quads (1 upper + 1 lower) from the same patient were randomly treated with (scaling and root planing [SRP]+PDT) together. The other 2 quadrants (1 upper + 1 lower) were treated by SRP only and selected to serve as controls. Clinical parameters including PI, GR, BOP, PPD and CAL and biological parameters (IL-1β) in the GCF were measured at baseline, then at, 2 and 6 months after therapy. Results: A statistically significant reduction in several clinical parameters as, BOP (P < 0.001), PI (P < 0.001), PPD (P < 0.001) and CAL (P < 0.001) in quadrant treated with SRP and adjunctive PDT when compared to control group treated with SRP alone was observed and both therapies showed non-statistically significant differences in the reduction of IL-1β level. Conclusion: The inclusion of PDT as an adjunctive measure to nonsurgical conventional periodontal treatment seems to be a useful therapeutic measure in refractory periodontitis treatment.